2017
DOI: 10.1016/j.envpol.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic exposure to air pollution and mortality in the acute respiratory distress syndrome

Abstract: The impact of chronic exposure to air pollution and outcomes in the acute respiratory distress syndrome (ARDS) is unknown. The Nationwide Inpatient Sample (NIS) from 2011 was utilized for this analysis. The NIS is a national database that captures 20% of all US in-patient hospitalizations from 47 states. Patients with ARDS who underwent mechanical ventilation from the highest 15 ozone pollution cities were compared with the rest of the country. Secondary analyses assessed outcomes of ARDS patients for ozone po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Twelve studies reported results for all-year O 3 exposure and all-cause mortality ( Table 3 a). We selected the most recent study results for meta-analyses, therefore three studies ( Health Effects Institute, 2000 , Jerrett et al, 2013 , Jerrett et al, 2009 ) were excluded and nine studies ( Health Effects Institute, 2000 , Lipsett et al, 2011 , Carey et al, 2013 , Turner et al, 2016 , Desikan et al, 2015 , Abbey et al, 1999 , Lipfert et al, 2006 , Tonne et al, 2016 , Rush et al, 2017 )were included for main analysis (note: one study ( Health Effects Institute, 2000 ) included two cohorts, results from one cohort was included, the other was excluded) ( Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies reported results for all-year O 3 exposure and all-cause mortality ( Table 3 a). We selected the most recent study results for meta-analyses, therefore three studies ( Health Effects Institute, 2000 , Jerrett et al, 2013 , Jerrett et al, 2009 ) were excluded and nine studies ( Health Effects Institute, 2000 , Lipsett et al, 2011 , Carey et al, 2013 , Turner et al, 2016 , Desikan et al, 2015 , Abbey et al, 1999 , Lipfert et al, 2006 , Tonne et al, 2016 , Rush et al, 2017 )were included for main analysis (note: one study ( Health Effects Institute, 2000 ) included two cohorts, results from one cohort was included, the other was excluded) ( Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…A small number of studies examined the shape of the concentration response relationships for O 3 and mortality. Turner 2016 ( Turner et al, 2016 ) analysing the American Cancer Society (ACS) cohort reported evidence that a threshold model (35 ppb) offered an improved fit over the linear model for annual O 3 concentrations and both respiratory and cardiovascular mortality ( Rush et al, 2017 ). Using thin-plate–spline models, Di ( Di et al, 2017 ) reported a relationship between O 3 and all-cause mortality that was almost linear, with no signal of a threshold down to 30 ppb.…”
Section: Resultsmentioning
confidence: 99%
“…Mortality from acute respiratory distress syndrome (ARDS) was associated with exposure to O3 and particulate matter. 99 After controlling for other (unstated) variables in the model, treatment in a hospital located in an area with high O3 was associated with an increased odds ratio (OR e ) of mortality of 1.11 (95% CI; 1.08-1.15, p < 0.01) for in-hospital mortality. Adjusting for all factors, for each 20-µg m -3 increment in the concentration of O3, the OR for mortality was 1.07 (95% CI; 1.06-1.08, p < 0.01).…”
Section: Overview Of Recent Human Health Studiesmentioning
confidence: 95%
“…For example, short‐term exposure to particulate matter (PM 2.5 ), NO 2 , and ozone is associated with lower forced vital capacity and lower forced expiratory volume . Additionally, a recent study reported that, in adult patients with acute respiratory distress syndrome, chronic exposure to air pollution (i.e., ozone and particulate matter (PM)) is associated with an increase rate of mortality . Importantly, the initiation of inflammatory responses within the lungs from pollutant exposure can affect other organ systems, contributing to further disease pathologies .…”
Section: Pulmonary Systemmentioning
confidence: 99%
“…8 Additionally, a recent study reported that, in adult patients with acute respiratory distress syndrome, chronic exposure to air pollution (i.e., ozone and particulate matter (PM)) is associated with an increase rate of mortality. 9 Importantly, the initiation of inflammatory responses within the lungs from pollutant exposure can affect other organ systems, contributing to further disease pathologies. 10 For example, acute or chronic exposure to airborne PM can accelerate the pathology of atherosclerosis through increases in vascular inflammation, macrophage infiltration, and generation of reactive oxygen species.…”
Section: Pulmonary Systemmentioning
confidence: 99%